Elections and democracy in the Kurdistan region of Iraq - Hamad, Tawfiq Rahman (KDI School, 2011)
Elections and democracy aren’t anything new to advanced democracies, however they are entirely different experiences to people of the Kurdistan Region; they are a new phenomenon and cultural experience. The Kurdistan Regional Government (KRG) was established in 1992 through an election in which people chose representatives through voting in a secret poll. The first election in the Kurdistan Region was indeed a milestone that turned Kurds from revolutionary groups into political parties that call for a functional government that implements principles of democracy. For the first time in a long time, Kurds in the region were optimistic about the future of their government and the democratization process. Unfortunately only a couple of years after the first Kurdish elections, a civil war broke out between the two ruling Kurdish parties, which coupled with some failures by the ruling cabinet the first few years after the elections, changed people’s enthusiasm and optimism towards the future of the KRG. The liberation of Iraq in 2003 and the American pledge to turn Iraq into a democratic country in the Middle East where Kurds no longer had to live as second class citizens. The situation meant that it was imperative that the two main Kurdish political parties work closely together, as the resolution of their internal disputes was necessary in order to achieve more gains in Baghdad as a united bloc. These actions were part of the democratization process that the Kurds strived to be part of, and the signing of the Washington Peace Agreement a few years prior to the liberation was crucial in helping establish the framework needed to end the conflicts between the two ruling Kurdish political parties. Since 1992, three separate elections have been held in the Kurdistan Region. However, the fact that over 19 years there has only been three elections means that a lot more could have been done and achieved had it not been for those internal issues. During the time of the civil war and the resulting internal problems, from 1992 to 2005, meant that the region only enjoyed two elections. The emergence of civil society, free media, and opposition groups in the past few years has meant that more and more people have taken and interest in, as well as recognizing the officially the Kurdistan Region Government as the legitimate democratic government representative of the people of the Kurdistan Region of Iraq. Currently political parties along with the government claim that there is democracy in the Kurdistan Region, nevertheless, there are civil societies, NGO’s and opposition groups can be heard debating the shortcomings and pitfalls of the democratization process in the region. Therefore, this paper will study and analyze the democratization process in the Kurdistan Region by using one independent variable- elections. Did the elections in the previous years help in improving democracy in the Kurdistan Region? Will democracy take root in the Kurdistan Region? If the question is affirmative, what are the tangible outcomes on the ground?
Thesis(Master) --KDI School:Master of Public Policy,2011